2007
DOI: 10.1016/j.ijporl.2007.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Newborn hearing screening in a South African private health care hospital

Abstract: Summary ObjectiveEarly Hearing Detection and Intervention (EHDI) programs are being established as part of the public health systems in increasing numbers of countries. In developing countries, however, little progress has been made towards implementing NHS programs and South Africa's public and private health care sectors is no exception.The current study presents the first report on a hospital-based UNHS program conducted in the South African private health care sector to provide preliminary results towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
58
0
10

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 27 publications
4
58
0
10
Order By: Relevance
“…Similarly a pilot infant hearing screening program at a public health care immunization clinic reported an even higher initial referral rate of 14% but only evaluated the initial 5 months of implementation [27]. Suboptimal referral rates reported by the remaining 20% of universal programs in this survey may have been due to factors such as poor data management or quality control, recently commenced programs, suboptimal screening technologies (such as AOAE implemented in NICUs) and test environment or procedural issues [16,[32][33].…”
Section: Referral and Follow-up Performance And Protocolsmentioning
confidence: 95%
See 4 more Smart Citations
“…Similarly a pilot infant hearing screening program at a public health care immunization clinic reported an even higher initial referral rate of 14% but only evaluated the initial 5 months of implementation [27]. Suboptimal referral rates reported by the remaining 20% of universal programs in this survey may have been due to factors such as poor data management or quality control, recently commenced programs, suboptimal screening technologies (such as AOAE implemented in NICUs) and test environment or procedural issues [16,[32][33].…”
Section: Referral and Follow-up Performance And Protocolsmentioning
confidence: 95%
“…Eighty per cent of these universal programs reported a referral rate for audiological and medical evaluation of less than 5%, on par with international benchmarks. Previously reported referral rates from South African studies have however been higher [27,32]. A review of a private health care universal newborn screening program indicated a referral rate of 11% across a 4 year analyses [32].…”
Section: Referral and Follow-up Performance And Protocolsmentioning
confidence: 96%
See 3 more Smart Citations